Effect of nursing interventions like meditation, progressive muscle relaxant exercises, and counselling on lifestyle and diet modification on marital relationship among women undergoing infertility treatment: randomized controlled trial: a pilot study - Aulakh, Rajbir Kaur; Uppal, Harjit Kaur; Pahwa, Sangeeta (International Journal Of Community Medicine And Public Health, 2023)
Background: Infertility has an impact on marital pleasure. Couples who are unhappy in their relationship are also more likely to have various negative psychological, social and physical health issues. Nurses can play a significant role in the management of infertility and its consequences. The recent study aimed to evaluate the effect of nursing interventions on marital relationship among women undergoing infertility treatment. Methods: By using a systematic sampling technique, 60 infertile women with marital disharmony (30 experimental and 30 control group) were included in the current randomized control trial. After getting their consent relationship assessment scale was used to estimate the marital relationship. The experimental group underwent the nursing intervention (Raja yoga meditation, progressive muscle relaxant exercises, advices on lifestyle and diet modification) for 5 subsequent visits apart from 15 days and the control group underwent standard medical care. Succeeding the intervention after one month’s last intervention, the relationship assessment scale was again applied to both groups. Results: Before the interventions both the groups were homogenous according to mean, SD and chi square values. After applications of dependent t-test, the mean score before and after nursing interventions the mean score was 13.70 SD 3.99 and 18.33 SD 2.89 respectively. The mean difference of marital relationship was 4.633 (t29=10.640, p=0.001). Independent t test was applied which reveals that the mean difference between experimental and control group was 3.867 (t58=4.215, p=0.001) which was statistically highly significant at 0.001 level. Conclusions: After implementing the nursing intervention, the study’s finding showed an improvement in the quality of marital relationship.